The frequency and phenological stage of foliar application of nutrients and biostimulant can increase sugarcane yield and biomass and bioenergy productions - Hervatin, Cleber de Morais [UNESP]; Prado Filho, Anibal Pacheco de Almeida [UNESP]; Momesso, Letusa; Jacomassi, Lucas Morais [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Wiley, 2024)
The impacts of sugarcane (Saccharum spp.) production include an extensive area of cultivation, high use of technology, and the generation of by-products that must be utilized. Achieving higher productivity while reducing the expansion of cultivation is challenging. A potential strategy for increasing sugarcane yields and productivity is the foliar application of nutrients and biostimulants at different stages of sugarcane growth. The present study assessed the impact of the foliar application of nutrients (N, B, Cu, and Zn) and a growth regulator as biostimulant (indole butyric acid, gibberellic acid, and kinetin) on sugarcane metabolism, stalk and sugar production, and quality. Field experiments were performed at 17 sites during four growing seasons (2017–2018, 2018–2019, 2019–2020, and 2020–2021) using sugarcane with three harvest times (early, mid-late, and late harvests). The treatments were as follows: (i) no foliar application of the biostimulant and nutrients (control), (ii) foliar application of the biostimulant and nutrients at the vegetative stage (VS) of sugarcane, (iii) foliar application of the biostimulant and nutrients at the maturation stage (MS) of sugarcane, and (iv) foliar application of the biostimulant and nutrients at both the vegetative and maturation stages (VMS). Foliar application did not increase ribulose 1,5-bisphosphate carboxylase activity but increased phosphoenolpyruvate carboxylase activity and the activities of the antioxidant enzymes. Peroxidase and catalase activities were higher, >100% and 45%, respectively, in VMS, whereas superoxide dismutase activity increased by 54% in MS compared with control. Consistent with these results, sugarcane had low hydrogen peroxide and malondialdehyde contents in VMS. In addition, the plant biometric parameters were highest in VMS, which sugarcane produced 105, 92, and 86 Mg stalk h−1 in early, mid-late, and late harvest seasons, respectively. In summary, the foliar application of the biostimulant and nutrients efficiently promoted the growth, productivity, and quality of early, mid-late, and late harvest seasons. The positive effects of foliar application on the enzymatic and physiological responses of sugarcane can be achieved when applications are performed in both the VMS in all harvest seasons.